"Unless you overdose or something you're not going to get help": What do adolescent experiences reveal about the mental health system in Perth, Western Australia?. (20th March 2020) - Platell, Monique; Martin, Karen; Fisher, Colleen; Cook, Angus
Abstract: Issues addressed: To explore adolescents' experiences of access to and continued use of mental health services, and identify factors influencing their perceived satisfaction with their care. This paper focusses on the role of organisational and policy‐level factors in the mental health system. Method: Qualitative semi‐structured face‐to‐face interviews with 22 adolescents aged 14‐18 years living in Perth, Western Australia. Results: Adolescents identified key policy, systemic and service‐based factors which influenced their access to and continued use of mental health services. These were strongly related to the processes of service intake, level of orientation towards person‐centred care and adequacy of service resourcing and funding. Areas of concern for adolescents included, complex service intake procedures, suboptimal mental health service environments, lack of client‐centred care and the quality of mental health support provided in school settings. Conclusions: Our research has identified a wide spectrum of factors influencing mental health service access and use amongst adolescents. The findings further support the growing national consensus for major reform to address the mental health needs of this age group. The current strengths within mental health services and the system identified by adolescents need to be supported and extended. So what?: Although there have been numerous recommendations on ways to improve mental health service access and ongoing engagement for Australian adolescents, a number of the major challenges faced by this high‐risk population have shown little improvement. The findings of this research indicate the importance of now moving towards implementing meaningful plans for action.